Solid Lipid Nanoparticles Coated with Glucosylated poly(2-oxazoline)s: A Supramolecular Toolbox Approach - Elter, Johanna K; Sedlák, František; Palušák, Tomáš; Bernardová, Nicol; Lobaz, Volodymyr; Tihlaříková, Eva; Neděla, Vilém; Šácha, Pavel; Hrubý, Martin (Biomacromolecules, 2025)
Multifunctional polymers are interesting substances for the formulation of drug molecules that cannot be administered in their pure form due to their pharmacokinetic profiles or side effects. Polymer-drug formulations can enhance pharmacological properties or create tissue specificity by encapsulating the drug into nanocontainers, or stabilizing nanoparticles for drug transport. We present the synthesis of multifunctional poly(2-ethyl-2-oxazoline-co-2-glyco-2-oxazoline)s containing two reactive end groups, and an additional hydrophobic anchor at one end of the molecule. These polymers were successfully used to stabilize (solid) lipid nanoparticles ((S)LNP) consisting of tetradecan-1-ol and cholesterol with their hydrophobic anchor. While the pure polymers interacted with GLUT1-expressing cell lines mainly based on their physicochemical properties, especially via interactions of the hydrophobic anchor with membranous compartments of the cells, LNP-cell interactions hinted toward an influence of the glucosylation on particle-cell interactions. The presented LNP are therefore promising systems for the delivery of drugs into GLUT1-expressing cell lines.
Keywords: Polymers; Nanoparticles; Hydrophobic and Hydrophilic Interactions; Drug Carriers; nanočástice; Lipids; lipidy; Oxazoles; lidé; přenašeč glukosy typ 1; oxazoly; nosiče léků; polymery; Glucose Transporter Type 1; Humans; hydrofobní a hydrofilní interakce